Synthesis of supported vertical NiS2 nanosheets for hydrogen evolution reaction in acidic and alkaline solution. Issue 42 (8th April 2015) - Wu, Xiaolin; Yang, Bin; Li, Zhongjian; Lei, Lecheng; Zhang, Xingwang
Abstract : We report a two-step synthesis to grow vertical NiS2 nanosheets on a graphite substrate, the NiS2 electrocatalyst showed excellent activity toward hydrogen evolution reaction in a wide pH range. Abstract : We synthesized vertical NiS2 nanosheets supported on a graphite substrate, which were fabricated by the surfactant-templated reaction followed by sulfidation. These nanosheets are efficient electrocatalysts for the hydrogen evolution reaction (HER). Structural characterization revealed that the as-grown NiS2 existed in a pyrite-structure and vertical nanosheets. The NiS2 electrocatalyst exhibited excellent activity and stability toward HER in both acidic and alkaline solution, with low Tafel slopes of ∼40 and ∼80 mV per decade, respectively.